Kecintaan Merek Lokal, Fashion Lifestyle, dan Minat Beli Sebagai Pembentuk Keputusan Pembelian Sneakers Ventela - Rika Dewi Apprilia; Renny Dwijayanti (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
The phenomenon of local brands is increasingly in demand and favored by the community, especially for teenagers. High enthusiasm has an impact on the rise of local brands in Indonesia. This study aims to determine the love of local brands (brand love), fashion lifestyle, and buying interest in purchasing decisions of Ventela sneakers. The population used in this study were all students of the UNESA who bought and felt interested in buying Ventela sneakers. The sampling technique used random sampling with a total sample size of 100 respondents from a population of 26,475 students. Data collection was carried out by surveying and distributing google form questionnaires. The analysis techniques used in this research are multiple regression analysis; f test and coefficient of determination; and hypothesis testing (t-test). The test results show that local brand love (brand love) is proven to have a significant and positive effect on purchasing decisions with the t-count value of 11.38. The fashion lifestyle variable is proven to have a significant and positive effect on purchasing decisions with the t-count value of 3.587.The purchase interest variable is proven to have a significant and positive effect on purchasing decisions with the t-count value of 4.468